KIF14 and citron kinase act together to promote efficient cytokinesis. - Gruneberg, U; Neef, R; Li, X; Chan, E; Chalamalasetty, R; Nigg, E; Barr, F (2006)
Multiple mitotic kinesins and microtubule-associated proteins (MAPs) act in concert to direct cytokinesis (Glotzer, M. 2005. Science. 307:1735-1739). In anaphase cells, many of these proteins associate with an antiparallel array of microtubules termed the central spindle. The MAP and microtubule-bundling protein PRC1 (protein-regulating cytokinesis 1) is one of the key molecules required for the integrity of this structure (Jiang, W., G. Jimenez, N.J. Wells, T.J. Hope, G.M. Wahl, T. Hunter, and R. Fukunaga. 1998. Mol. Cell. 2:877-885; Mollinari, C., J.P. Kleman, W. Jiang, G. Schoehn, T. Hunter, and R.L. Margolis. 2002. J. Cell Biol. 157:1175-1186). In this study, we identify an interaction between endogenous PRC1 and the previously uncharacterized kinesin KIF14 as well as other mitotic kinesins (MKlp1/CHO1, MKlp2, and KIF4) with known functions in cytokinesis (Hill, E., M. Clarke, and F.A. Barr. 2000. EMBO J. 19:5711-5719; Matuliene, J., and R. Kuriyama. 2002. Mol. Biol. Cell. 13:1832-1845; Kurasawa, Y., W.C. Earnshaw, Y. Mochizuki, N. Dohmae, and K. Todokoro. 2004. EMBO J. 23:3237-3248). We find that KIF14 targets to the central spindle via its interaction with PRC1 and has an essential function in cytokinesis. In KIF14-depleted cells, citron kinase but not other components of the central spindle and cleavage furrow fail to localize. Furthermore, the localization of KIF14 and citron kinase to the central spindle and midbody is codependent, and they form a complex depending on the activation state of citron kinase. Contrary to a previous study (Di Cunto, F., S. Imarisio, E. Hirsch, V. Broccoli, A. Bulfone, A. Migheli, C. Atzori, E. Turco, R. Triolo, G.P. Dotto, et al. 2000. Neuron. 28:115-127), we find a general requirement for citron kinase in human cell division. Together, these findings identify a novel pathway required for efficient cytokinesis.